Argentina : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper describes economic developments in Argentina during the 1990s. The paper describes the main elements of the economic strategy put in place since 1991, highlighting the relation between supply and demand aspects of this strategy. The paper highlights that the Convertibility Plan and associated reforms introduced in Argentina starting in 1991 succeeded in accelerating growth, stopping a protracted inflation-that had twice already resulted in hyperinflation-and fundamentally changing the nature of the economy. The paper also analyzes the financial policies and the consolidation of the banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet